Memahami Kehadiran Allah Melalui Peran Malaikat - Piter, Paulus (Perspektif, 2016)
God is present in all things. The presence of God is understood by human beings in their own ways. A human manner that understands the presence of God can be found in the role of angels. An angel is a real embodiment of the presence of God. Certainly, the presence of God requires instruments or ways to understand. The instrument or medium can be found in the angel itself, because the angel exists in human being as “The way of Representation” of God. To understand the presence of God through the role of an angel is still actual. It is still actual, because the role of an angel gives the answer to show virtues or values and examplar lives. An angel who is presenting a representative image is understood on its existence through human prayer and faith. Only in prayer and faith the meaning of God’s presence in an angel can be easier perceived by men and women of faith in their daily life.